2019
DOI: 10.3389/fpls.2019.00343
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem Services Related to Carbon Cycling – Modeling Present and Future Impacts in Boreal Forests

Abstract: Forests regulate climate, as carbon, water and nutrient fluxes are modified by physiological processes of vegetation and soil. Forests also provide renewable raw material, food, and recreational possibilities. Rapid climate warming projected for the boreal zone may change the provision of these ecosystem services. We demonstrate model based estimates of present and future ecosystem services related to carbon cycling of boreal forests. The services were derived from biophysical variables calculated by two dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 114 publications
(141 reference statements)
2
33
0
2
Order By: Relevance
“…8), also investigated by Ruosteenoja et al (2017). These effects are also detrimental for winter harvesting and wood quality, as suggested by Holmberg et al (2019). Manninen et al (2019) reported lengthened snow melting periods for some regions in Finland for 1982-2016.…”
Section: Impact To Ecosystemsmentioning
confidence: 89%
“…8), also investigated by Ruosteenoja et al (2017). These effects are also detrimental for winter harvesting and wood quality, as suggested by Holmberg et al (2019). Manninen et al (2019) reported lengthened snow melting periods for some regions in Finland for 1982-2016.…”
Section: Impact To Ecosystemsmentioning
confidence: 89%
“…In wild plants, the earlier onset of thermal springs does not necessarily increase the total annual growth, since water resources in the soil may then be depleted earlier, resulting in drought stress (Buermann et al, 2018). Even so, according to Holmberg et al (2019) warming is likely to increase the carbon sink in boreal forests; particularly the tree biomass (Sievänen et al, 2014). However, the long-lasting thermal autumns act to enhance the total ecosystem respiration more than photosynthesis, which turns the carbon balance more negative in that season (Vesala et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…3), but the effect pales in comparison to the examined management actions. This underlines the importance of proper forest management for provisioning services (Snell et al, 2018;Holmberg et al, 2019). This is illustrated by the relative NEE pathways (Fig.…”
Section: Impact To Ecosystemsmentioning
confidence: 74%
“…Assessment of uncertainties related to carbon budgets and growing season length together with water and snow conditions is important in estimating the forests ability to provide ecosystem services related to e.g. carbon sequestration, wood harvesting, maintaining habitats and promoting nature tourism (Snell et al, 2018;Holmberg et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation